Histomorphometric Study of Bone Healing Around Laminar Implants in Experimental Diabetes - Giglio, Maximo Juan Evaristo (2000)
The aim of this study was to evaluate the effects of experimental diabetes on the healing period leading to osseointegration. Wistar rats were injected with a single dose of streptozotocin (STZ); body weight and food intake were assessed every 48 hours. On days 2, 12, 26, and 42 post-STZ, glucemia, plasma hemoglobin, and urea were determined. Twelve days post-STZ, a titanium laminar implant was placed in the right tibia of each rat. Two groups of 20 rats each were killed on days 14 and 30 postimplantation, respectively. Results (ANOVA test) showed STZ-treated rats to have 1) a significant decrease in body weight; 2) an increase in food intake; 3) normal hemoglobin and plasma urea values; 4) a significant increase in glucemia; and 5) a decrease in tibiae length. Microscopic evaluation 14 days postimplantation revealed the presence of woven bone, and, at 30 days, laminar bone was in contact with the implant. Our findings show that, in this model of periimplant bone repair and under the experimental conditions stated herein, STZ-induced diabetes retards periimplant bone healing.